Awareness, Perceptions and Challenges of E-Learning among Faculty of Science Undergraduates of Federal University Oye-Ekiti, Nigeria - Olajide, Olabode; Omolehin, Rotimi James; Ozimede Zuwelatu , Anyakorah; Ojo, Funmilola Adeola (Communicate: Journal of Library and Information Science, 2023)
This study examined awareness, perceptions and challenges of e-learning among FUOYE undergraduates during the 2023 general election break in Nigeria.The descriptive survey research design was adopted for this study. All Faculty of Science undergraduates, FUOYEformed the population of the study. A structured questionnaire was made available to students via Google Forms. A total of 370 respondents responded to the questionnaire.Data werearranged and analysed using quantitative analysis to generate frequencies and percentages, and presented in the form of charts and tables.The findings of this study revealed that majority of the students were highly and very highly aware of only two (WhatsApp and Telegram) e-learning platforms out of nine identified e-platforms. Findings also revealed that as some students have favourable perceptions towards e-learning platforms, so some were still indifferent to e-learning.Findings further revealed that majority of Faculty of Science undergraduates, FUOYE encountered myriad of challenges that hindered them from using e-learning platform. By implications, this study is worthwhile in providing a platform for university management to resolve the challenges hindering students from using e-learning platforms for academic purposes, and equally have reasons why e-learning platforms must be fully adopted in teaching and learning activities among undergraduates.